2004
DOI: 10.1002/hep.20448
|View full text |Cite
|
Sign up to set email alerts
|

Pge1–Induced No Reduces Apoptosis by D–Galactosamine Through Attenuation of Nf–Kb and Nos–2 Expression in Rat Hepatocytes

Abstract: P rostaglandins are biologically active polyunsaturated fatty acids derived from arachidonic acid present in most mammalian tissues. 1 Prostaglandin E 1 (PGE 1 ) reduces liver injury induced experimentally 2 and in fulminant viral hepatitis in humans. 3 PGE 1 exerts most of its effects by promoting membrane stabilization, 4 , hepatocyte proliferation, 5 vasodilation, 6 and inhibition of fibrogenesis. 7 The preadministration of PGE 1 also reduces liver injury through the enhancement of inducible NO synthase (NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…activation of soluble guanylate cyclase and inhibition of cytochrome c oxidase, or by producing covalent protein post-translational modifications, such as cysteine S-nitrosylation and tyrosine nitration, that can alter protein function [18]. NO has been shown to exert pro-apoptotic and anti-apoptotic effects in cultured hepatocytes [19][20][21]. GCDCA prevented NOS-2 expression and NO production in cytokine-treated rat hepatocytes [22].…”
Section: Introductionmentioning
confidence: 99%
“…activation of soluble guanylate cyclase and inhibition of cytochrome c oxidase, or by producing covalent protein post-translational modifications, such as cysteine S-nitrosylation and tyrosine nitration, that can alter protein function [18]. NO has been shown to exert pro-apoptotic and anti-apoptotic effects in cultured hepatocytes [19][20][21]. GCDCA prevented NOS-2 expression and NO production in cytokine-treated rat hepatocytes [22].…”
Section: Introductionmentioning
confidence: 99%
“…According to this data, adiponectin inhibited hepatic NF-kB signaling in ConA-induced acute liver failure. Recent reports demonstrated that hepatoprotective and antiapoptotic molecules such as S-Adenosylmethionine and PGE1 may reduce NF-kB activation in hepatocytes [16,17]. However, further signaling pathways being involved in the anti-apoptotic effects of adiponectin in hepatocytes remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocytes were cultured in Dulbecco's modified Eagle's medium containing 10% fetal bovine serum (Invitrogen). Hepatocytes were incubated for 24 h post-isolation before experiments (8,31).…”
Section: Methodsmentioning
confidence: 99%
“…Activation of both or either one of these transcription factors can elicit MCP-1 gene expression (27)(28)(29). Both AP-1 and NF-B are present in hepatocytes and can be activated in response to various stimuli (30,31). Hcy-induced MCP-1 expression in vascular smooth cells and monocytes/macrophages appears to be mediated via NF-B activation (29,32).…”
Section: Homocysteine (Hcy)mentioning
confidence: 99%